The Current Use of Biomedical Cell Products for Cancer Treatment - E. A. Ustyugova; M. V. Savkina; A. A. Goryaev; V. P. Bondarev; V. A. Merkulov; E. V. Melnikova (Биопрепараты: Профилактика, диагностика, лечение, 2019)
Cancer remains one of the leading causes of death. Conventional treatment methods, including radiation and chemotherapy, have limited effectiveness. Therefore, the development of novel approaches to cancer treatment is an urgent challenge. Biomedical cell products (BMCPs) which include adoptive cell therapy (ACT) and dendritic cells vaccines (DCVs) are considered a promising area of research. The aim of the study was to review current ideas about the principles of BMCP therapy, as well as clinical experience with cell-based products used for cancer treatment. The paper summarises the results of clinical use of tumor-infiltrating lymphocytes (TIL-therapy), genetically modified T-cells that express tumour antigen-specific receptors (TCR/CAR T-therapy), as well as DCVs. The use of human immune cells genetically modified ex vivo is a novel and promising approach to cancer treatment. The main analysed ACT approaches which are based on the use of genetically modified T-lymphocytes have some benefits and drawbacks. The paper discusses the methods of BMCP production, provides data on the effectiveness of ACT and DCVs. It pays special attention to safety concerns associated with each treatment method, as well as to other factors limiting their clinical use. It is expected that the main areas of further research will be aimed at increasing BMCP efficacy and reducing adverse reactions.